Julian Tenison Woods: lyricist and missionary - O'Brien, Roderick (The Australasian Catholic record, 2018)
Among the treasures at the Congregational Archives of the Sisters of St Joseph of the Sacred Heart in North Sydney is a booklet, a hymnal: a collection of hymns and sacred songs attributed to Fr Julian Tenison Woods.1 The purpose of this short article is to introduce one of those hymns, and provide some information about poetry and songs in Woods's life and mission. I am grateful to the archivist for making this booklet available. Introducing this particular hymn, "Longing to Go", also gives us some insight into Woods's spirituality regarding death and regarding mission.